ANTI-INFLAMMATORY ACTIVITY OF STEM BARK DICHLOROMETHANE FRACTION Syzygium samarangense EXTRACT AS COX-2 INHIBITOR: A BIOINFORMATICS APPROACH - Ahmad Misbakhus Sururi; M. Raihan; Elvira Ratna Aisa; Frisca Nadya Safitri; Irene Cornelia Constaty; Tukiran (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Syzygium samarangense is a plant that is rich in flavonoid compounds. Previous researchrevealed that the dichloromethane fraction from the stem bark extract contained fourbioactive compounds, namely, pinocembrin, uvangoletin, stercurensin, and aurentiacin,which had good antioxidant activity. However, research on the potential of these fourcompounds as an anti-inflammatory has not been revealed. This study aims to continueprevious research in revealing the potential of compounds in the dichloromethane fractionof S. samarangense extract as an anti-inflammatory agent in silico COX-2 inhibitors. Thisstudy uses in silico biocomputation, including drug-likeness analysis and molecular dockinganalysis using COX-2 protein and the control drug rofecoxib. The results showed that thereare compounds that have the potential as anti-inflammatory compounds, namelypinocembrin. However, further studies, such as in vitro and in vivo, are still needed to revealits potential as an anti-inflammatory agent